The Influence of Digital Marketing and Product Variations on Purchasing Decisions Moderated by Packaging on Lifebuoy Soap Moderated by Packaging on Lifebuoy Soap - Indriani, Dede; Hutauruk, Basar Maringan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of technology today makes consumers utilize technology to fulfill their daily lives. Some consumers use information technology facilities to fulfill the information they need, one of which is the use of the Internet. Technological advances from the internet have led to changes in consumer lifestyles. A total of 99 respondents were included in the quantitative research model employed for this study. SmartPLS data processing software was used to process the research, and a Google Form was used to collect the data. Purposive sampling is used with non-probability sampling in the sampling procedure. SmartPLS analysis is carried out in three stages, namely Outer Model Analysis (Validity Test, Discriminant Validity, and Reliability Test), Inner Model Analysis (R-Square), and Hypothesis Testing. The hypothesis test results show that the t-statistic value of 0.478 is greater than the T table 0.195 and the P-value value is 0.633 so the first hypothesis states that digital marketing on Lifebuoy soap is rejected. The hypothesis test results show that the t-statistic value of 0.877 is greater than the Ttable 0.195 and the P-values are 0.381 so the second hypothesis which states that digital marketing on Lifebuoy soap is rejected. The hypothesis test results show that the t-statistic value of 0.393 is greater than the Ttable 0.195 and the P-values are 0.694 so the third hypothesis which states that digital marketing moderated by packaging on Lifebuoy soap is rejected. The hypothesis test results show that the t-statistic value of 0.083 is greater than the Ttable 0.195 and the P-value is 0.934 so the third hypothesis which states that product variations moderated by the packaging on Lifebouy soap are rejected.